The relationship between visionary leadership of student leaders in youth organizations and identity towards the values of nationalism in Malaysia - Ibrahim, Abdullah; Safian, Anuar; Zulkafli, Nur Fazliza; Md Rami, Ahmad Aizuddin; Wan Mokhtar, Wan Khairul Aiman (Microthink Institute, 2022)
Students play an important role as potential leaders of the country and need to have a high level of understanding and appreciation of their obligations as citizens of Malaysia. This study examines the influence of student leadership on nationalism and identity education among those active youth leaders who are still studying on the East Coast of Malaysia. The cross-sectional survey method was applied in the data collection process involving the Visionary Youth Leadership Survey questionnaire established by Joseph in 2007, an Identity Model questionnaire developed by Corner in 1993, and a Nationalist Value Model questionnaire from the National Policy Publishing Division in 2009. A total of 326 youth leaders were still studying and leading youth associations in their respective regions by the time of the study. Findings show visionary leadership of youth leaders has proven to have a 47% influence on identity. In addition, Visionary Youth Leadership also influenced 76% of nationalism. In conclusion, the findings demonstrate that Nationalism plays a mediator in the relationship between the Visionary Leadership of Youth Leaders and Identity Education where Nationalism acts as a partial mediator. This study can be used by national leaders, university management, and education departments as a guide in assessing the leadership aspects of national leaders. In addition, this study can serve as a basic reference for enhancing the various disciplines of leadership management based on nationalism and identity education as the foundation for the development of a leader's identity.